Analisis Kondisi Fisik Atlet Karate Kabupaten Tuban Menghadapi Porprov 2025 Melalui Biomotorik Daya Tahan Kardiovaskuler - R. Zufar Fulvian Noor Haq; Noortje Anita Kumaat (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The martial art of Karate is an expression and human work that is used to protect oneself or defend oneself without using weapons. This research was conducted with the aim of exploring and analyzing the use of physical conditioning programs for Tuban Karate athletes who will face Porprov 2025 through aspects of biomotor endurance. The research participants consisted of 20 athletes, with 10 female athletes and 10 male athletes, who were preparing for Porprov 2025. The research method used was quantitative descriptive. The research results showed that the MFT test on Tuban Regency Karate athletes, consisting of 20 athletes (10 men and 10 women), showed an average height of 167.75 cm and an average body weight of 60.80 kg. The average body mass index (BMI) value of Karate athletes in Tuban Regency is 21.59. The highest and lowest values ​​for aerobic capacity (VO2Max) are 46.2 and 28. The average overall ability of Tuban Regency Karate athletes, with an age range of 16-22 years, is 34.3 ml/kg/min, which is included in the category good (Good). The conclusion of this research is that Tuban Regency Karate athletes, aged 16-22 years, have good VO2Max abilities when facing Porprov 2025.